Design and Generation of MLPA Probe Sets for Combined Copy Number and Small-Mutation Analysis of Human Genes: EGFR as an Example. (2010) - Marcinkowska, Malgorzata; Wong, Kwok-Kin; Kwiatkowski, David J.; Kozlowski, Piotr
Abstract : Multiplex ligation-dependent probe amplification (MLPA) is a multiplex copy number analysis method that is routinely used to identify large mutations in many clinical and research labs. One of the most important drawbacks of the standard MLPA setup is a complicated, and therefore expensive, procedure of generating long MLPA probes. This drawback substantially limits the applicability of MLPA to those genomic regions for which ready-to-use commercial kits are available. Here we present a simple protocol for designing MLPA probe sets that are composed entirely of short oligonucleotide half-probes generated through chemical synthesis. As an example, we present the design and generation of an MLPA assay for parallel copy number and small-mutation analysis of the EGFR gene.